Dampak Pelatihan Kerja, Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan pada PTPN III Medan - Minne Sotha Roma Ito Br Sinaga; Herlina Novita; Rifaldi Marbun (IPM2KPE, 2023)
This research aims to determine the effect of Job Training (Variable X1), Discipline (X2), and Work Motivation (X3) on employee performance. The method used in this research is quantitative methods. The data collection techniques used by researchers in this research are through interviews, questionnaires and documentation. Data analysis techniques start from data preparation, data tabulation to the testing stage. The results of the research calculations of multiple linear regression analysis show that the coefficient of determination (R2) can be obtained from the variables. This research aims to determine the influence of Job Training (Variable X1), Discipline (X2), and Work Motivation (X3) which influence 79.3% (0.793) on employee performance (Y), the remaining 20.7% is influenced by other factors outside this research. Conclusion, Job Training (Variable X1), Discipline (X2), and Work Motivation (X3) influence employee performance. Keywords: Work Discipline, Employee Performance, Motivation, Job Training